Diseño estructural de un coliseo multiusos para la escuela "Celiano Monge" - Cumbajín Escobar, Carlos Ricardo (2010)
Proposes the structural design of a multipurpose coliseum for the school "Celiano Monje" which is one of the long-established educational centers that serve the southern sector of Quito, today currently changing to the denomination of Educational Institution Fiscal "Celiano Monge", since by its popularity it needs an expansion in its infrastructure that in spite of its proximity to the capital city has deficiencies among them the one of a suitable premises so that it allows to fulfill with such mission.